Perbandingan Tingkat Keterampilan Teknik Setiap Posisi Dalam Bola Basket Antara Atlet Porda Putri Kota Bandung Dengan Kabupaten Bandung Barat - Mochamad Kiki Rizki; Nina Sutresna; Alen Rismayadi; Berliana Berliana (Jurnal Kepelatihan Olahraga, 2022)
This research uses a comparative descriptive method with a quantitative approach to compare technical skills among basketball positions in female athletes from Porda Bandung City and Bandung Regency West. The study aims to identify technical differences in basketball positions such as point guard, shooting guard, small forward, power forward, and center. Data was collected from 15 athletes in each team through tests and documentation. The findings show significant differences in technical skills, particularly in passing, dribbling, lay up, under the ring, and shooting, with variations between the teams for each position. Technical skills significantly impact team success and achievements in basketball.